Penerapan Relaksasi Benson Pada Pasien Gagal Ginjal Kronik Yang Menjalankan Hemodialisa Melalui Aplikasi Teori Model Jean Watson Rumah Sakit Bhayangkara Tahun 2025 - Rilda Dwi Tania; Tita Septi Handayani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Chronic kidney disease is a non-communicable disease whose prevalence continues to increase in Indonesia and has a significant impact on the quality of life of patients, especially those undergoing haemodialysis therapy. Long-term haemodialysis can cause anxiety due to lifestyle changes, dependence on equipment, and psychological pressure. This study aims to determine the effect of applying the Benson relaxation technique in reducing anxiety levels in chronic kidney failure patients undergoing haemodialysis, through Jean Watson's caring model theory approach. The study was conducted observationally on two respondents at Bhayangkara Hospital in Bengkulu City in 2025. The intervention was carried out over two days using structured Benson relaxation techniques, including components of a calm atmosphere, repetition of words based on beliefs, passive attitudes, and comfortable positions.The evaluation results showed a decrease in signs of anxiety such as restlessness, tension, and sleep disturbances, as well as improvements in physiological parameters. This intervention proved to be effective as a non-pharmacological therapy in improving patient comfort and calmness. The integration of Jean Watson's holistic approach strengthened the effectiveness of Benson relaxation in nursing care. It is hoped that these results can serve as a reference for nursing practice in managing anxiety in patients with chronic kidney failure.